Evaluation of Carbon Aerogel Manufacturing Process in Order to Desalination of Saline and Brackish Water in Laboratory Scale - Massoudinejad, Mohamadreza; Hashempour, Yalda; Mohammad, Hamed (Salehan Institute of Higher Education, 2018)
Carbon aerogel its fabrication and characterization and its uses in this process were studied for desalinating of saline and brackish water. The carbon aerogel manufacturing process involves the polymerization and pyrolysis of the mixture of resorcinol and formaldehyde. Carbon aerogels were analyzed using BET, BJH, and T-plot after construction. The effect of various parameters (including the influent salt concentration, the intensity of electric current flow, the distance between the electrodes and pH) on salt adsorption were studied. Analysis of BET/BJH shown that the surface of aerogel was 677.8 m2/g. much of porosity in the samples of carbon aerogel were between 1-2 nm, namely micro-pour and a similar level 0f 456 m2/gr is dedicated to micro-pour, with a correlation coefficient (r) equal to 94.5. According to the results, it seems that carbon aerogel electrodes have a good structure in desalination of brackish and saline water.